2018
DOI: 10.1530/ey.15.15.12
|View full text |Cite
|
Sign up to set email alerts
|

TAp63 contributes to sexual dimorphism in POMC neuron functions and energy homeostasis

et al.

Abstract: Sexual dimorphism exists in energy balance, but the underlying mechanisms remain unclear. Here we show that the female mice have more pro-opiomelanocortin (POMC) neurons in the arcuate nucleus of hypothalamus than males, and female POMC neurons display higher neural activities, compared to male counterparts. Strikingly, deletion of the transcription factor, TAp63, in POMC neurons confers "male-like" diet-induced obesity (DIO) in female mice associated with decreased POMC neural activities; but the same deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Table 1 gives the benchmark of our FeFETs and FeCaps. Chou et al 37 demonstrated the largest 2Pr value, but due to a lower BDS value, it did not achieve the highest I ON /I OFF ratio and MW value. In contrast, Kim et al 36 showed the largest BDS with a higher I ON /I OFF ratio, but due to lower polarization, it did not achieve MW > 2 V. In our work, using surface morphology and stress engineering, with large a polarization and a high BDS value, we achieved the highest I ON /I OFF ratio, a large MW, a low SS, and a good nonlinearity of conductance modulation in the HZO/IGZO-based FeFET.…”
Section: Acs Appliedmentioning
confidence: 88%
“…Table 1 gives the benchmark of our FeFETs and FeCaps. Chou et al 37 demonstrated the largest 2Pr value, but due to a lower BDS value, it did not achieve the highest I ON /I OFF ratio and MW value. In contrast, Kim et al 36 showed the largest BDS with a higher I ON /I OFF ratio, but due to lower polarization, it did not achieve MW > 2 V. In our work, using surface morphology and stress engineering, with large a polarization and a high BDS value, we achieved the highest I ON /I OFF ratio, a large MW, a low SS, and a good nonlinearity of conductance modulation in the HZO/IGZO-based FeFET.…”
Section: Acs Appliedmentioning
confidence: 88%
“…This extremely significant difference (p < 0.0001) is the result of the anti-adhesive membrane on the surface of organ, which is similar to our previous work. [30] Both the liver and kidney are ruptured during the peeling test, and it is impossible to record the data (Figure 4e). Obviously, the adhesive energy of IFA hydrogel is greater than the cohesion of the liver or kidney.…”
Section: Wet-adhesive Diversificationmentioning
confidence: 99%
“…As shown in Figure 6f, urea is a strong hydrogen bond acceptor and donor, which can serve as a hydrogen bond breaker; [35] while, ionic solution (PBS) can shield electrostatic effects to a certain extent. [30] In depth, reduced L-Glutathione (GSH) can easily cut disulfide bonds at the interface (Figure 6g).…”
Section: Controllable Adhesionmentioning
confidence: 99%